2012
DOI: 10.1186/cc11868
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and early evolution of organ failure in the intensive care unit and their relation to outcome

Abstract: IntroductionRecognition of patterns of organ failure may be useful in characterizing the clinical course of critically ill patients. We investigated the patterns of early changes in organ dysfunction/failure in intensive care unit (ICU) patients and their relation to outcome.MethodsUsing the database from a large prospective European study, we studied 2,933 patients who had stayed more than 48 hours in the ICU and described patterns of organ failure and their relation to outcome. Patients were divided into thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
113
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(123 citation statements)
references
References 20 publications
5
113
1
4
Order By: Relevance
“…The Sequential Organ Failure Assessment (SOFA) score is a tool developed to quantitatively describe the time course of organ dysfunction [14]. A previous study found that the SOFA score was an independent predictor of developing early acute respiratory failure in a heterogeneous population of critically ill patients [21]. Our data suggest that a 10% increase in the risk of POPCs is likely for each unit increase in the SOFA score at ICU admission.…”
Section: Discussionmentioning
confidence: 58%
“…The Sequential Organ Failure Assessment (SOFA) score is a tool developed to quantitatively describe the time course of organ dysfunction [14]. A previous study found that the SOFA score was an independent predictor of developing early acute respiratory failure in a heterogeneous population of critically ill patients [21]. Our data suggest that a 10% increase in the risk of POPCs is likely for each unit increase in the SOFA score at ICU admission.…”
Section: Discussionmentioning
confidence: 58%
“…3,10,11 As an example, Cardoso et al 11 have reported that each hour of delay in admission of a patient to the ICU is associated with a 1.5% increase in the risk of death in the ICU and a 1% increase in Hospital mortality. Likewise, Sakr et al 12 have found mortality among critically ill patients to be clearly related to the initial evolution of organ failure and the SOFA score at the time of admission to the ICU. If readmission to the ICU proves necessary, there is a four-fold increase in mortality risk, and the length of Hospital stay is moreover doubled.…”
Section: Palabras Clavementioning
confidence: 96%
“…Multiple organ dysfunction syndrome remains the lead cause of morbidity and mortality in intensive care patients [1]. The etiology of MODS is multifactorial and is likely precipitated by a combination of tissue hypoperfusion, hypoxia, metabolic derangement, and mitochondrial dysfunction [2].…”
Section: General Principlesmentioning
confidence: 99%